THE ROLE OF CUSTOMER TRUST IN MEDIATING VISUAL CONTENT QUALITY AND SERVICE QUALITY ON PURCHASING DECISIONS AT WEDDING DOCUMENTATION SERVICES - Asep Munajat; Asep Muhamad Ramdan; Tetty Sufianty Zafar (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Wedding documentation is mandatory and much sought after by couples who want to capture every moment of their marriage, but consumer behavior in the use of products or services always changes with the times. This study aims to determine how much customer trust mediates visual content quality and service quality in users of wedding video documentation services. The grand theory of this research is marketing management theory and this research is quantitative with a correlational approach method. Research data was obtained by distributing online using probability sampling techniques to 225 respondents. The data analysis technique in this study is the Structural Equational Modelling (SEM) technique using IBM SPSS AMOS 23 software. The results showed that the role of customer trust has a positive and significant effect and is effectively used in the relationship between visual content marketing and service quality to improve purchase decisions in wedding documentation video services for Cineos Wedding Film customer. The findings of this study indicate that consumer trust acts as a significant mediator in the relationship between visual content quality and service quality on service purchase decisions. In other words, consumer decisions to use wedding documentation services are strongly influenced by the level of trust formed through the presentation of quality cinematic video content, professional and responsive services. The implications of this research are important for service providers, such as Cineos Wedding Film to consistently maintain, improve visual and service quality to build customer trust that can encourage sustainable service usage decisions.